Enhancement of the Oxygen Reduction Reaction (ORR) on a PtPb Nanoparticle /TiO2/Cup-Stacked Carbon Nanotube Composite in Acidic Aqueous Solutions based on the Electronic Interaction between PtPb and TiO2. (2nd August 2016) - Ando, Fuma; Gunji, Takao; Tanabe, Toyokazu; Kaneko, Shingo; Takeda, Tsuyoshi; Ohsaka, Takeo; Matsumoto, Futoshi
Abstract : PtPb ordered intermetallic nanoparticles (NPs) deposited on titanium oxide (TiO2 )/cup-stacked carbon nanotubes (CSCNT), PtPb NPs/TiO2 /CSCNT, were prepared by synthesis of TiO2 with Ti-alkoxide under Ar atmosphere, by photodeposition of Pt NPs on the TiO2 surface of TiO2 /CSCNT and by selective deposition of Pb atoms to Pt NPs with polyol method. The PtPb NPs/TiO2 /CSCNT is, at the first potential cycle, inferior to bench-marked Pt NPs/carbon black (Pt/CB) in the oxygen reduction reaction (ORR) in acidic aqueous solution, whereas after 100 potential cycles between 0.3 and 1.1 V ( vs. RHE), the ORR was accelerated largely when compared with the Pt/CB. The ORR activity of PtPb NPs/CB degraded with potential cycle due to the dissolution of Pb from the surface of PtPb NPs. On the other hand, the dissolution of Pb was suppressed to a lesser degree on the PtPb NPs deposited on TiO2 by the interaction between PtPb and TiO2 . The dealloyed NP surface composed of the Pt atoms and the residual Pb atoms is considered to bring about the enhancement of ORR.